A RETROSPECTIVE REVIEW OF OPEN PROSTATECTOMY IN A RESOURCE-CONSTRAINED SETTING. - Msibi, Sifiso; Singh, Avikar (Student’s Journal of Health Research Africa, 2023)
Background: Open prostatectomy is an important treatment modality for prostate disease in resource-constrained settings, where access to minimally invasive surgery is limited. We conducted a review of open prostatectomies at a South African hospital. Methods: We reviewed the medical charts of 54 patients who underwent open prostatectomy at St. Aidan’s Hospital in South Africa between 2015 and 2019. Data collected for each patient included demographic characteristics, comorbidity, prostate-specific antigen measurements, prostate volume measurements, preoperative catheterisation, indication for surgery, surgical approach, duration of surgery, postoperative length of stay, histological findings, and postoperative Clavien-Dindo complications. We analyzed the collected data with descriptive statistics. Results: The median age was 68.5 years old. Most patients were Black Africans (57.4%). Hypertension was the most common comorbidity (50.0%). Most patients (83.4%) had prostate-specific antigen levels of 10 ng/mL or less, and prostate volumes of 60-100 mL (57.4%). Preoperative catheterisation was common (77.8%). Lower urinary tract symptoms and failed medical therapy (74.1%) was the most frequent indication for surgery. All patients had surgery via the suprapubic approach, with surgery lasting >120 minutes for two-thirds of patients. Postoperative length of stay was 6-9 days for nearly half of the study sample (48.1%). Almost all patients had a histological diagnosis of benign prostate hyperplasia (94.4%). Postoperative complications were frequent and mostly minor (infection or blood transfusions). Conclusion: We confirm that open prostatectomy is still a relevant, safe, and effective method for managing prostate disease in resource-constrained settings. We recommend that open prostatectomy still be considered a primary treatment modality for prostate disease in developing countries until minimally invasive methods become more widely available.